Challenging Class Barriers in Jane Austen’s Mansfield Park - Yalçın Erden (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Jane Austen can be regarded as an author renowned for her conventional novels at first glance. Nevertheless, reading Austen in a profound way reveals that there lies a hidden critical voice against the irregularities of society. In this article, the novel, Mansfield Park, is analysed to demonstrate how the author interrogates class as a constructed notion by employing unusual techniques which are reminiscent of postmodernist devices. After the function of ex-centric characters, Fanny Price and James Rushworth, is focused on, the role of the intertextual references employed by Austen in unearthing artificial class distinctions is examined. It is concluded that the author implicitly challenges the class-oriented social system of her age.